Bounded rationality: Difficulties to make decisions in Design for sustainability - Ana Cravino; Jorge Pokropek (RChD: Creación y Pensamiento, 2018)
The purpose of this article is to reflect on the different approaches involved in an environmentally conscious design. It is known that the variability of the data referred to the sustainability of a material and the reliability of the same constitutes an obstacle for the decision making. That is why sustainable design, often, resorts to formal aspects that highlight the recycling or reuse of materials with a strongly artisan look.